Cardiac Tamponade Associated with the Presentation of Anaplastic Large Cell Lymphoma in a 2-Year-Old Child - Gema Mira-Perceval Juan; Pedro J. Alcalá Minagorre; Ana M. Huertas Sánchez; Sheila Segura Sánchez; Silvia López Iniesta; Francisco J. De León Marrero; Estela Costa Navarro; María Niveiro de Jaime (Hindawi Limited, 2015)
The anaplastic large cell lymphoma is a rare entity in pediatric patients. We present an unusual case of pericardial involvement, quite uncommon as extranodal presentation of this type of disorder, that provoked a life-risk situation requiring an urgent pericardiocentesis. To our knowledge, this is the first report on a child with pericardial involvement without an associated cardiac mass secondary to anaplastic large cell lymphoma in pediatric age. We report the case of a 21-month-old Caucasian male infant with cardiac tamponade associated with the presentation of anaplastic large cell lymphoma. Initially, the child presented with 24-day prolonged fever syndrome, cutaneous lesions associated with hepatomegaly, inguinal adenopathies, and pneumonia. After a 21-day asymptomatic period, polypnea and tachycardia were detected in a clinical check-up. Chest X-ray revealed a remarkable increase of the cardiothoracic index. The anaplastic large cell lymphoma has a high incidence of extranodal involvement but myocardial or pericardial involvements are rare. For this reason, we recommend a close monitoring of patients with a differential diagnosis of anaplastic large cell lymphoma.